2010
DOI: 10.1093/intimm/dxq012
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Th1-biased cytokine production by  -carba-GalCer, a neoglycolipid ligand for NKT cells

Abstract: NKT cells are characterized by their production of both T(h)1 and T(h)2 cytokines immediately after stimulation with alpha-galactosylceramide (alpha-GalCer), which is composed of alpha-galactopyranose linked to ceramide (itself composed of sphingosine and fatty-acyl chains); the chain length of the ceramide varies and this affects the ability of alpha-GalCer to stimulate cytokine production. However, the contribution of its galactopyranose sugar moiety remains unclear. We synthesized alpha-carba-GalCer, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Conversely, a-C-GalCer, a C-glycoside (carbon glycoside) analogue of a-GalCer, activated iNK T cells at very low concentrations and promoted Th1 responses in vivo [31]. More recently, Tashiro et al [32] synthesized a-carbaGalCer, which strongly induced NK T cell-mediated Th1 cytokines in a fashion similar to a-C-GalCer [32].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a-C-GalCer, a C-glycoside (carbon glycoside) analogue of a-GalCer, activated iNK T cells at very low concentrations and promoted Th1 responses in vivo [31]. More recently, Tashiro et al [32] synthesized a-carbaGalCer, which strongly induced NK T cell-mediated Th1 cytokines in a fashion similar to a-C-GalCer [32].…”
Section: Introductionmentioning
confidence: 99%
“…Although its synthesis is not easy, RCAI-56 (13) can also induce potent Th1-cytokine production. 75,76,80) Recently, Yoshiga et al reported that 13 suppressed murine collagen-induced arthritis by enhancing the Th1 response. 160) RCAI-61 (14), developed by a simple modification, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As we expected, this ethereal analog 13 resisted enzymatic degradation in a liver microsome assay more than 1, and induced potent Th1-cytokine production not only in mice but also in humans, in contrast to -CGalCer (10). 80) According to the crystal structures of binary CD1d/-galactosyl ceramide complexes, 18,19) the glycosidic oxygen atom is involved in a hydrogenbonding network, and might be important in making a stable complex, especially with human CD1d. Detailed docking model study and elucidation and comparison of the crystal structure of human CD1d/13/TCR to those of 10 should clarify the differences in bioactivity between -C-GalCer (10) and RCAI-56 (13).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In this in vivo cytokine study, we used similar time frame for PBS-44 as for αGalCer. 29,30 Further, considering the slow release of the NanoVac, we chose 24 hours posttreatment. As shown in Figure 4A, B, the levels of IFN-γ and IL-4 in the NanoVac-treated cohort increased …”
Section: Nanovac Induces the Proliferation Of Nkt Cells And Productiomentioning
confidence: 99%